Inorganic PM10 emission from the combustion of individual mallee components and whole-tree biomass - Gao, Xiangpeng; Rahim, Usman; Chen, Xixia; Wu, Hongwei (Combustion Institute, 2017)
© 2016 Elsevier Ltd.This contribution reports the emission of inorganic particulate matter (PM) with an aerodynamic diameter <10µm (PM10) from the combustion of both individual mallee components and whole-tree biomass. Three major components of a mallee tree, namely bark, leaf, and wood, were size-reduced to 75-150µm and mixed at a dry mass ratio of 15% bark:35% leaf:50% wood, which is close to the real mallee's composition, to prepare a whole-tree biomass. The three individual mallee components and the whole-tree biomass were combusted in a laboratory-scale drop-tube furnace at 1400°C in air to produce inorganic PM10 for further quantification and characterization. The results demonstrate that, whereas the particle size distributions of the PM10 from the combustion of the bark, leaf and wood components generally follow a bimodal distribution, the yields of PM0.1, PM0.1-1, PM1, PM1-10, PM2.5, and PM10 from the three mallee components are quite different. On the bases of dry biomass and useful energy input, the yields of the PM of various size fractions studied follow a sequence of the bark>the leaf>the wood, consistent with that of the ash contents in the three components. Oppositely, the ash-based yields of PM0.1, PM0.1-1, PM1, PM1-10, PM2.5, and PM10 from the wood are substantially higher than those from the bark and the leaf. No obvious synergetic effect among different mallee components in PM10 emission is observed during the whole-tree biomass combustion, enabling the prediction of the PM10 yield from the whole-tree biomass combustion based on that from the individual mallee components.